The challenges of urban ecological sanitation : lessons from the Erdos eco-town project - Rosemarin, Arno; McConville, Jennifer R., 1978; Flores, Amparo E. (Amparo Espino), 1975; Qiang, Zhu
Includes bibliographical references (pages 97-101)